Dependence Analysis of the Solutions on the Parameters of Fractional Delay Differential Equations (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, we investigate the dependence of the solutions onthe parameters (order, initial function, right-hand function) offractional delay differential equations (FDDEs) with the Caputofractional derivative. Some results including an estimate of thesolutions of FDDEs are given respectively. Theoretical results are verified by some numerical examples.